When goodbye comes too soon: How to wrap up science projects quickly - Hagenauer, Megan Hastings; Winham, Stacey J.; Freeman, Alexandra L. J.; Sternberg, Paul W.; Kolber, Benedict J. (PLOS Biology, 2025)
Science projects are designed and funded on the scale of years, so what happens when researchers need to finish prematurely? This Community Page discusses solutions for quickly documenting partially finished projects, and for publishing ‘as you go’ in an uncertain environment.